Funcionamiento familiar en familias víctimas de abuso sexual intrafamiliar-incesto - Ibeth Villanueva Sarmiento (Psicogente, 2011)
Abstract This article of research describes family functioning in victims of domestic sexual abuse (incest) in the city of Barranquilla and the following dimension were taken in account: a) Familiar adaptation to face up conflict situations, b) Level of participation and emotional growth in each one of the members and c) Affective relationships and commitments between family members. That is a descriptive study and Familiar APGAR test, which measures the rank of family functionality, proposed by Gabriel Smilkstein (1978), modify for Colombia by Liliana Arias (2006) was used. The sample was ten (10) members of families, victims of domestic sexual abuse (incest) that received the clinical intervention en the “Centro de Atención Integral e Investigación para Víctimas de Abuso Sexual” (CAIVAS) in the Barranquilla city. The results shows that 20% of the total population presents a severe family dysfunction, a 0% a moderate family dysfunction, a 20% a slight dysfunction and finally a 60% presented a normal familiar functionality.